Changes in Gene Expression of Whiteflies, Bemisia tabaci MED Feeding on Tomato Plants Infected by One of the Criniviruses, Tomato Chlorosis Virus through Transcriptome Analysis - Jing Zhao; Xiaoan Sun; Huijie Dai; Xianping Zhang; Dezhen Zhang; Xiaoping Zhu (International Journal of Genomics)
Tomato chlorosis virus (ToCV), transmitted by the whitefly, Bemisia tabaci (Gennadius; Hemiptera: Aleyrodidae) has been continuously emerging on tomato plants and causing a significant economic loss throughout China. In the current study, RNA-Seq analysis was used to explore the gene expression profiles of B. tabaci Mediterranean (MED) that fed on both ToCV-infected and -uninfected tomato plants for 6, 12, 24, and 48 hours, respectively. The results revealed that dynamic changes occurred in the gene expressions of whiteflies at different time intervals after they acquired the virus. A total of 1709, 461, 4548, and 1748 differentially expressed genes (DEGs) were identified after a 6, 12, 24, and 48 hours feeding interval for the viral acquisition, respectively. The least number of expressed genes appeared in whiteflies with the 12 hours feeding treatment, and the largest numbers of those found in those with 24 hours feeding treatment. Kyoto Encyclopedia of Genes and Genomes pathway analysis revealed that B. tabaci MED responded to ToCV acquisition through altering its nerve system development, fertility, detoxification, glucose metabolism, and immune function before it lost its ability to transmit the virus. The number of DEGs, degree of differential gene expressions, expression level of the same gene, involved biological processes, and metabolic functions in whiteflies post the 12 hours feeding, and viral acquisition were different from those from other three feeding treatments, which could be a significant finding suggesting an effective control of B. tabaci MED should be done less than 12 hours after whiteflies started feeding on ToCV-infected tomatoes. Our results further provided a clarified understanding in how B. tabaci was protected from viral acquisitions through comparison of the differential profile of gene expressions in whiteflies feeding on plants that were infected by semipersistent viruses.